Symbolic Violence in Online Media Short Stories: An Analysis of Habitus, Capital, and Field from Pierre Bourdieu’s Perspective - Rahmawati; R, Mantasia; Sakaria (Universitas Cokroaminoto Palopo, 2026)
This study aims to analyze the forms of symbolic violence in online media short stories using Pierre Bourdieu’s theoretical perspective, particularly the concepts of habitus, capital, and field. The research employs a qualitative method with a sociological approach to literature. The data sources consist of two short stories, namely Perempuan dalam Bejana and Buaian Rahim Patriarki by Ni Wayan Wijayanti. Data were collected through reading and note-taking techniques, while data analysis was conducted using a descriptive-analytical method. The results show that symbolic violence in the short stories is manifested in the forms of forced marriage, the subordination of women, the silencing of women’s voices, and the objectification of women. This violence occurs due to the internalization of patriarchal habitus, which leads women to perceive domination as something natural. In addition, male domination is reinforced by the possession of economic and social capital, enabling control over women. The family field becomes the primary space where symbolic violence occurs, as unequal power relations are normalized within the domestic structure. Thus, online media short stories function not only as literary works but also as representations of social reality that depict gender inequality and hidden practices of domination.